Flash flood forecasting over complex terrain : with an assessment of the Sulphur Mountain NEXRAD in Southern California (National Academies Press, 2005)
"The nation's network of more than 130 Next Generation Radars (NEXRADs) is used to detect wind and precipitation to help National Weather Service forecasters monitor and predict flash floods and other storms. This book assesses the performance of the Sulphur Mountain NEXRAD in Southern California, which has been scrutinized for its ability to detect precipitation in the atmosphere below 6000 feet. The book finds that the Sulphur Mountain NEXRAD provides crucial coverage of the lower atmosphere and is appropriately situated to assist the Los Angeles-Oxnard National Weather Service Forecast Office in successfully forecasting and warning of flash floods. The book concludes that, in general, NEXRAD technology is effective in mountainous terrain but can be improved."--Publisher's description